Effect of Acid Treatment in Dye Loading Capacity of Spin Coated ZnO Film - Baduwal, Harka Bahadur; Shrestha, Pitamber; Chaudhary, Dinesh Kumar; Mulmi, Deependra Das; Joshi, Leela Pradhan (Amrit Research Journal, 2020)
In recent times, the research on ZnO is growing tremendously, because of its potential use in many applications such as optical devices, dye sensitized solar cell (DSSC), gas sensors and biomedical. ZnO thin films of various thicknesses were prepared by the spin coating method using the zinc acetate precursor with diethanolamine and ethanol. The structural and optical characterizations of as-prepared ZnO films carried out using XRD and UV-Vis spectrophotometer, respectively. The XRD results showed polycrystalline wurtzite structure of ZnO. The average crystallite size of ZnO as calculated using Debye Scherrer’s formula was 26 nm. The optical band gap of ZnO was found to decrease with film thickness. The dye extracted from the leaves of Tectona Grandis (Sagun) which possesses a high and wide absorbance was used in this experiment. The study on the effect of acid treatment on ZnO films in dye loading showed enhanced absorbance in acid treated ZnO as compared to untreated ZnO.